Enteroviral meningitis without pleocytosis in children. Issue 10 (19th July 2012) - Yun, Ki Wook; Choi, Eun Hwa; Cheon, Doo Sung; Lee, Jina; Choi, Chang Won; Hwang, Hee; Kim, Beyong Il; Park, Kyoung Un; Park, Sung Sup; Lee, Hoan Jong
Abstract : Objectives: This study aims to describe the clinical characteristics of enteroviral meningitis in association with the absence of cerebrospinal fluid (CSF) pleocytosis. Design: This was a retrospective analysis of databases of patients diagnosed with enteroviral meningitis by CSF reverse transcription-PCR testing. Presence of CSF non-pleocytosis at each age group was analysed by use of the two criteria. Clinical variables were compared with regard to the presence of CSF pleocytosis. Multiple logistic regression analysis was used to identify factors that were associated with CSF pleocytosis. Setting: Two hospitals in South Korea, between January 2008 and August 2011. Patients: 390 infants and children with enteroviral meningitis. Interventions: None. Main outcome measures: Proportion of enteroviral meningitis without CSF pleocytosis. Results: Among the 390 patients with enteroviral meningitis, 16–18% did not have CSF pleocytosis. In particular, CSF pleocytosis was not present in 68–77% of the neonates with enteroviral meningitis, demonstrating that the proportion of CSF pleocytosis decreased significantly with age (p<0.001). In multivariate models, younger age (adjusted OR 0.981; 95% CI 0.973 to 0.989), lower peripheral white blood cell count (adjusted OR 0.843; 95% CI 0.791 to 0.899), and shorter interval between onset and lumbar puncture (adjusted OR 0.527; 95% CI 0.315 to 0.882) were associated with the absence of CSF pleocytosis in enteroviral meningitis. Conclusions: This study demonstrated high proportion of non-pleocytic enteroviral meningitis in young infants and identified several clinical factors that contributed to the absence of CSF pleocytosis. We suggest that CSF enterovirus PCR testing is likely to detect more cases of enteroviral meningitis, especially in young infants.